Improving database design teaching in secondary education: action research implementation for documentation of didactic requirements and strategies. - Fessakis, George; Dimitracopoulou, Angélique; Komis, Vassilis (Computers in Human Behavior, 2005)
Database design and use has educational interest for utilitarian and learning reasons. Database technology has significant economic impact and the demand for database design cannot be covered by the existent educated experts. Furthermore, the database management systems available at schools could be used for the design and implementation of high quality learning activities. Databases are general purpose modeling environments that enable problem solving using conceptual frameworks closer to the solver and the problem than the machine architecture. Databases design introduction in the curricula of secondary education programs raises educational research questions. Research questions concern the didactics of the subject as well as the value of database design based learning activities. In this paper, we present some of the more significant findings of an action research concerning the database design in secondary education. Research questions concern the ideas of students about databases and their difficulties during database design. Data, collected using a variety of research activities, are analyzed and discussed and teaching strategies are proposed. Copyright (c) 2004 Elsevier Ltd